The Distribution of Minerals in Crucial Plant Parts of Various Elderberry (Sambucus spp.) Interspecific Hybrids - Imenšek, Nataša (Plants (Basel), 2021)
In view of growing requirements of the food industry regarding elderberries (genus Sambucus), a need to increase their productivity and improve their chemical composition has emerged. With this purpose in mind, numerous elderberry interspecific hybrids have been created. In the present work, the content of minerals in their crucial plant parts was studied. It was also investigated whether superior genotypes regarding the mineral composition of berries and inflorescences could be predicted at early stages of plant development. The results showed that elderberry leaves contained the highest amounts of Ca, Mg, Mn, Zn, and Sr, while K and P were predominant in fruit stalks. Fe and Al prevailed in roots and Cu in bark. Although berries showed lower mineral content compared to other plant parts, their mineral content is not negligible and could be comparable to other commonly consumed berries. Genotypes with a favorable mineral content of inflorescences and berries could be predicted on the basis of known mineral composition of their shoots and leaves. The study also indicates that S. nigra genotypes and the majority of interspecific hybrids analyzed are suitable for further genetic breeding or cultivation.